Unveiling the impact of the bias-dependent charge neutrality point on graphene based multi-transistor applications. (17th August 2021) - Pasadas, Francisco; Medina-Rull, Alberto; Feijoo, Pedro Carlos; Pacheco-Sanchez, Anibal; Marin, Enrique G.; Ruiz, Francisco G.; Rodriguez, Noel; Godoy, Andrés; Jiménez, David
Abstract: The Dirac voltage of a graphene field-effect transistor (GFET) stands for the gate bias that sets the charge neutrality condition in the channel, thus resulting in a minimum conductivity. Controlling its dependence on the terminal biases is crucial for the design and optimization of radio-frequency applications based on multiple GFETs. However, the previous analysis of such dependence carried out for single devices is uncomplete and if not properly understood could result in circuit designs with poor performance. The control of the Dirac point shift (DPS) is particularly important for the deployment of graphene-based differential circuit topologies where keeping a strict symmetry between the electrically balanced branches is essential for exploiting the advantages of such topologies. This note sheds light on the impact of terminal biases on the DPS in a real device and sets a rigorous methodology to control it so to eventually optimize and exploit the performance of radio-frequency applications based on GFETs.